The effectiveness of the composite material for restoration of permanent teeth in children - Terekhova , Т. Н.; Melnikova, Е. И.; Klenovskaya, М. И. (Actual Dentistry, 2022)
The aim of the study was to evaluate the clinical effectiveness of “Admira Fusion” composite material for the restoration of permanent teeth in children. Material and methods. 143 permanent teeth in 52 children and adolescents (average age 13.4 years) were treated using universal nanohybrid “Admira Fusion” composite. Restorations assessment was carried out in 12 and 24 months according to Ryge criteria. Results. In has found that caries experience of permanent teeth in children and adolescents participating in the study according to the DMFT index is 4.3±1.4, which corresponds to the moderate level of caries intensity. The level of oral hygiene according to the OHI-S index is 0.7±0.1, which is assessed as satisfactory hygiene. It has been analyzed that in children and adolescents 51.05 % caries affected teeth were the first permanent molars (73 teeth) and 27.27 % – the second permanent molars (39 teeth). In 11.89 % of clinical cases caries was detected in the first premolars (17 teeth) and in 9.79 % (14 teeth) – in the incisors of the upper jaw. The analysis of lesions localization on the surfaces of permanent teeth has indicated that in children and adolescents most often in 60.46 % treated teeth caries was detected on the occlusal surfaces (I class by Black). In 27.9 % of the restored teeth, combined lesions of the occlusal and proximal surfaces (Black, class II) were recorded: 11.53 % on the distal occlusal surfaces and 16.27 % on the medial-occlusal surfaces. Isolated lesions of the medial (14.65 %) and vestibular (6.98 %) surfaces (Black, class V) were noted rarely. It has been found high effectiveness of the proposed treatment using universal nanohybrid material «Admira Fusion» for restoration in two years. 100 % retention of restorations were detected. There were no found complaints of toothache or loss of fillings in 100 % clinical cases. 100 % of the restorations were noted with good edge adaptation and anatomical shape. There were no signs of secondary caries in all clinical cases. Evaluation of the shade adaptation after 2 years has shown that 93.01±2.13 % composite restorations was impossible to recognize without a mirror, and 6.99±2.13 % (10) of the restorations had color deviations in contrast to the tooth tissues, but no more than a change in their shade or transparency which is within the normal color and transparency of the tooth. The color deviations were more often registered in the occlusal proximal and the occlusal restoration (II Black class, 10.3±4.83 % and Black I class, 5.8±2.51 % accordingly). Color assessment of the filling’ edge after 2 years showed no change in the transition from the restoration to the tooth tissues during visual inspection with a mirror in 89.51±2.56 % of the nanohybrid restorations. Discoloration in the area of the filling-tooth junction not extending in depth was detected in 10.49±2.56 % (15) fillings. Most often, edge discoloration was observed in class II restorations by Black (11 teeth) and less often in class I restorations by Black (4 teeth). The evaluation of the surface quality of the fillings has shown, that 2 years after the treatment, 100 % of the restorations were with a shine and smooth surface, did not require correction or re-treatment, and also had no signs of irritation of the surrounding soft tissues. Conclusion. The use of “Admira Fusion” composite for the restoration of permanent teeth in children provides high clinical efficacy in 89–93 % of clinical cases. Thus, the “Admira Fusion” universal nanohybrid material is characterized by great working properties with good adaptation to the tooth hard tissues, retains its aesthetic characteristics in the oral cavity for 2 years. Convenience in work and technical ability to use any adhesive systems make it the material of choice in pediatric dentistry.